ANALYSIS OF Fe, Zn, AND Cr AT SOME FRACTIONATED PROTEINS IN SPONGE AGELAS NAKAMURAI - Anita Nur Ramadhani; Alfian Noor; Maming Gaffar (Marina Chimica Acta, 2014)
This research aims to analyze the concentration of metals Fe, Zn, and Cr in protein fractions of sponge Agelas nakamurai from Kapoposang Island, Spermonde archipelago. Protein samples were extracted, fractionated using various saturated ammonium sulphate (SAS) concentration, namely 0-20%, 20-40%, 40-60% and 60-80%, then purified by dialysis using celophane membranes. Each fraction was digested using microwave before metal analysis using ICP OES (Inductively Coupled Plasma Optical Emission Spectroscopy). The results have shown that highest iron concentration was found in 20-40% fraction, 28.2 µg/L, while lowest one was in 60-80% fraction, 2.39 µg/L. For Zn, its highest concentration were found 20-40% fraction,  9.42 µg/L and the lowest one was 40-60%, 3.66 µg/L. On the other hand, the concentration of Cr was found highest at 20-40% fraction, 2.28 µg/L, while its lowest amount was at  60-80% fraction, 0.238 µg/L. In the meantime, its high- est antibacterial activity was at 0-20% fraction examined in Salmonella thypusa with inhibition diameter was 7,00 mm, where the amount of essential metals Fe, Zn and Cr are 17,2 µg/L, 6,32 µg/L, 1,47 µg/L. It was concluded that the essential metals investigated were coexisted and distrib- uted in several protein fractions and its bioactive properties.Keywords   :  Agelas  nakamurai,  Bioactive  protein,  essential  metals, ICP-OES,  Kapoposang Island